Future Opportunities in the Field of Drug Delivery Research - Kohn, Joachim; Michniak-Kohn, Bozena (Journal of Medical Science, 2023)
Much of the priorities in drug delivery research are focused on targeted drug delivery for cancer therapies and a wide range of controlled drug release systems for commonly used active pharmaceutical ingredients (APIs). In this “thousand words article” we highlight some of the emerging health threats and future opportunities for drug delivery research. Important emerging health threats include viral pandemics beyond COVID, antibiotic-resistant pathogens, the need for new antifungal therapies, and emerging diseases caused by increasing pollution and climate change. Fundamentally new drugs may be needed. For example, one little known research effort focuses on the development of new antibiotics based on metal-organic frameworks. Finally, new delivery approaches will be needed. This is illustrated by the development of a topical peptide delivery system as a wound dressing for burn patients, combining biotechnology (a new peptide) with polymer science (a new topical delivery system) to address a medical need (burn injury) for which there is currently no effective treatment. Another important trend is the shift in our collective understanding of impact, moving away from “counting papers” to considering the societal benefit of the research including its potential for commercialization. To remain relevant in the coming decade, we need to anticipate and embrace future challenges. This is particularly important for younger scientists.